Contribution of Farming Enterprises of the Small Farmers towards Household Food Security - Kobir, H; Rahman, MZ; Islam, MS; Sultana, N; Al-Musa, MAA (Journal of Environmental Science and Natural Resources, 2013)
The study was to determine the contribution of farming enterprises of small farmers towards household food security and explore relationship with their selected characteristics. Besides, attempts were also made to ascertain the problems faced by the small farmers in achieving household food security. The highest proportion (57%) of the small farmers was in medium while 27% of them were in low category in achieving household food security. Only 44.78% of annual dietary needs of the family were fulfilled from the farming enterprises of the small farmers and more than half of the requirements remained unsatisfied. Among the four sectors of farming enterprises, the highest proportion (41.70%) was contributed by crops alone. Among ten characteristics of the small farmers, farm size and annual family income were positively correlated but family size, annual dietary needs of the family and practiced cropping intensity showed negative relationship with the contribution of farming enterprises towards household food security. The rest characteristics viz. age, education, credit received daily time allocation in farm works and exposure to farming information of the respondents showed insignificant correlation with their achievement of contribution of their farming enterprises towards the household food security. The major problems faced by the small farmers in achieving household food security were inadequate land for farming, inadequate training facilities, lack of contact with communication media, insufficient credit and lack of knowledge of different aspects of improved farming enterprises. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14837 J. Environ. Sci. & Natural Resources, 5(2): 323-328 2012